La valeur de la scintigraphic du foie pour le diagnostic de Péchinococcose hépatique - Ikkos, D.; Gonticas, S.; Gatsou, P. (Nuklearmedizin - NuclearMedicine, 1970)
The diagnostic value of liver scanning for hydatid cysts of the liver was examined by comparing the preoperative scintigrams and the surgical findings in 100 consecutive cases operated upon for hydatid cysts of the liver. False results were found in 10 cases (false positive in 1 and false negative in 9 cases). In the remaining 90 cases the scans had demonstrated the presence of pathological findings supporting the diagnosis of hydatid cysts. In 66 of these 90 cases the number, location and size of the cyst(s) were accurately defined by the scan, while in the remaining 24 cases there was a discrepancy between the scan and the surgical findings as to the number of the cysts. The effect of the number and location of the cysts on the accuracy of the scan diagnosis was analyzed.